ANALISIS HUKUM ISLAM TENTANG ZAKAT PROFESI (ZAKAT PENDAPATAN) DI INDONESIA: ANALISIS HUKUM ISLAM TENTANG ZAKAT PROFESI (ZAKAT PENDAPATAN) DI INDONESIA - muhammad luqman hakim (JINGJI : Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
Professional zakat, also known as income zakat, is an evolution of zakat jurisprudence that emerged as a reaction to contemporary economic dynamics. From the perspective of Islamic jurisprudence, professional zakat is classified as part of zakat mal, which is mandated on income generated from professional endeavors, including salaries, honoraria, or performance-based compensation. According to scientific research conducted by Damayanti (2020), Nikmah and Fahrullah (2024), and Balkis and Aji (2024), professional zakat has a qiyas foundation similar to zakat applicable to agriculture and trade, as both categories derive their legitimacy from human labor and effort. Contemporary scholars, including Yusuf al-Qaradawi and Wahbah al-Zuhaili, argue that the obligation to pay professional zakat is triggered when income reaches a threshold equivalent to 85 grams of gold and meets the criteria of one transportation. The regulatory framework in Indonesia, as outlined in Law No. 23 of 2011 on Zakat Management, reinforces this perspective by establishing a legal framework for the collection and distribution of professional zakat through officially recognized zakat institutions. As a result, the concept of zakat related to professions exemplifies the adaptability of Islamic law in addressing the complexities of modern economic progress while firmly upholding the basic principles of justice and social welfare.